2018
DOI: 10.1210/js.2017-00370
|View full text |Cite
|
Sign up to set email alerts
|

Na+/Ca2+ Exchanger a Druggable Target to Promote β-Cell Proliferation and Function

Abstract: An important feature of type 2 diabetes is a decrease in β-cell mass. Therefore, it is essential to find new approaches to stimulate β-cell proliferation. We have previously shown that heterozygous inactivation of the Na+/Ca2+ exchanger (isoform 1; NCX1), a protein responsible for Ca2+ extrusion from cells, increases β-cell proliferation, mass, and function in mice. Here, we show that Ncx1 inactivation also increases β-cell proliferation in 2-year-old mice and that NCX1 inhibition in adult mice by four small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Further, heterozygous inactivation of the Na + /Ca 2+ exchanger isoform 1 (NCX1) increased their proliferation in mice [ 113 ]. Based on these findings, the same group found that chemical inhibition of NCX1 had the same effect [ 114 ].…”
Section: β-Cell Mitogens: the Road To Clinical Translationmentioning
confidence: 99%
“…Further, heterozygous inactivation of the Na + /Ca 2+ exchanger isoform 1 (NCX1) increased their proliferation in mice [ 113 ]. Based on these findings, the same group found that chemical inhibition of NCX1 had the same effect [ 114 ].…”
Section: β-Cell Mitogens: the Road To Clinical Translationmentioning
confidence: 99%
“…200 Based on these observations, recently the same group reported that chemical inhibition of the same target using phenoxybenzamyl-derivatives small molecules promoted beta-cell proliferation in mice. 201 The use of a more stringent approach resulted in the identification of glucocorticoids as inducers of beta-cell proliferation in rats and humans. 202 In this particular instance, beta cells from adult rats and humans were FACS purified and treated with a collection of 1280 bioactive compounds (LOPAC) for 6 days.…”
Section: Beta-cell Proliferationmentioning
confidence: 99%
“…Migrating endothelial cells have higher expression of PMCA at their leading edges to maintain low basal [Ca 2+ ]i levels thereby, preventing continued activation of Myosin Light Chain Kinase (MLCK) and extended contraction of the cell membrane at the migration frontier [ 47 ]. On the other hand, NCX1 inhibition and thus impairment of [Ca 2+ ]i extrusion allows the proliferation of pancreatic beta cells [ 48 ].…”
Section: Intracellular Ca 2+ Buffers In Normal Cellsmentioning
confidence: 99%